A Factors Affecting Village Government Finances - Suhendri, Hendrik; Andika Putri, Sri; Ina Kaka, Apliana (International Journal of Management and Business, 2024)
The aim of this research is to determine the influence of organizational behavior and the implementation of an accounting system on village government finances. The research method used is a quantitative method based on the positivism paradigm. Meanwhile, to test the existing hypothesis, multiple regression analysis was used. The design of this research is a case studyThe research results show that partially organizational behavior variables have an influence on village government finances. In addition, the variable implementation of the accounting system partially influences village government finances. Not only that, simultaneously these two variables also influence village government finances.